A survey of medicinal plants for diabetes treating from Chana and Nathawee district, Songkhla province, Thailand. (4th November 2015) - Neamsuvan, Oratai; Madeebing, Nareerat; Mah, Latepah; Lateh, Wasana
Abstract: Ethnopharmacological relevance: Diabetes mellitus is a chronic disease which cannot be cured and must be suffered for whole life. Nowadays, many patients wanting to treat themselves by herbal medicine are increasing. Therefore, surveying of medicinal plants for treating diabetes and disseminating the knowledge, might give people more choice to consume herbs. The purposes of this qualitative study were to compile the medicinal plants and their folk use to treat diabetes by local healers in Chana and Nathawee district, Songkhla province. Materials and methods: Semi-structured interviews were used to gather about the local names, parts of plants used, preparation and use method, and local properties. Descriptive statistics, use value and interpretation were used to analyze the data. Results: A total of 38 species belonging to 37 genera in 28 families were used as herbs for treating diabetes. The family mostly used as herbal medicine was Rubiaceae (4 species; 10.53%). The part of herbal medicine mostly used was the root (8 speciess; 21.05%). Decoction and drinking were the most favorite preparation form and use method. Interestingly, the most used herbal plant is Lagerstraemia speciose Pers (0.83 of Use Value). Conclusion: It was found that the local healers possess the different knowledge based on their experience received secretly from the family and adapted by themselves. Thus, this study is important due to assistance for collecting the variety of knowledge before disappearing. Graphical abstract: